The 10-Repeat 3′-UTR VNTR Polymorphism in the SLC6A3 Gene May Confer Protection Against Parkinson’s Disease: A Meta-analysis - Zeng, Qiaoli; Ning, Fan; Gu, Shanshan; Zeng, Qiaodi; Chen, Riling; Peng, Liuquan; Zou, Dehua; Ma, Guoda; Wang, Yajun (Frontiers in Genetics, 2021)
The dopamine transporter (DAT) is encoded by the SLC6A3 gene and plays an important role in the regulation of the neurotransmitter dopamine. The SLC6A3 gene contains several repetition alleles (3–11 repeats) of a 40-base pair variable number of tandem repeats (VNTR) in the 3′-untranslated region (3′-UTR), which may affect DAT expression levels. The 10-repeat allele could play a protective role against PD. However, inconsistent findings have been reported. Methods: A comprehensive meta-analysis was performed to accurately estimate the association between the 10-repeat allele of the 3′-UTR VNTR in SLC6A3 and PD among four different genetic models. Results: This meta-analysis included a total of 3,142 patients and 3,496 controls. We observed a significant difference between patients and controls for the allele model (10R vs. all others: OR = 0.860, 95% CI: 0.771–0.958, P = 0.006), pseudodominant model (10R/10R + 10R/9R vs. all others: OR = 0.781, 95% CI: 0.641–0.952, P = 0.014) and pseudorecessive model (10R/10R vs. all others: OR = 0.858, 95% CI: 0.760–0.969, P = 0.013) using a fixed effects model. No significant differences were observed under the pseudocodominant model (10R/9R vs. all others: OR = 1.079, 95% CI: 0.945–1.233, P = 0.262). By subgroup analysis, the 10R, 10R/10R and 10R/9R genotypes were found to be significantly different from PD in Asian populations. Conclusion: Our findings suggest that the SLC6A3 10-repeat may be a protective factor in susceptibility to PD.